CFD Analysis on Course Stability of a Towed Ship Incorporated with Symmetrical Bridle Towline - Fitriadhy, Ahmad; Aldin, Nur Adlina; Mansor, Nurul Aqilah (CFD Letters, 2021)
Instability of a towed ship presented in the form of her vigorous sway motions may be susceptible to a serious towing accident especially in the restricted waterways. To prevent such phenomenon occurs, a comprehensive investigation on course stability of a towed ship is obviously required. This paper presents Computational Fluid Dynamic (CFD) approach to analyze the course stability of the towed ship associated with symmetrical bridle towline configuration. Several towing parameters such as various towline lengths and towing’s velocities have been taken into account in the computational simulation. Here, a towed ship was designated as 1B (barge) and employed in the simulations. The results revealed that the subsequent increase of the towline length has degraded the course stability of the towed ship, which imposed upon the increase of the sway motion of the towed ship by 1.95%. In addition to the increase of the towing’s velocity from V_s=0.509 m/s up to 0.655 m/s, the course stability of the towed ship has led to the unstable towing condition indicated by 10.77% increment of the yaw motion. It can be concluded that the course stability of the towed barge is degraded, attributed by larger towline length and towing’s velocity. These findings are beneficial and contribute to ship towing system safety navigation.